PRINCIPLES OF RESTORATION OF FERTILITY IN YOUNG AGE WOMEN WITH POLYCYSTIC OVARIAN SYNDROME - Assistant Ibragimova Nadiya Sabirovna; Assistant Karimova Linara Alikhanovna (Scholar Express Journals, 2023)
Polycystic ovary syndrome (PCOS) is a multifactorial heterogeneous pathology characterized by chronic anovulation, menstrual irregularities, infertility, ovarian cystic changes, and hyperandrogenism. The frequency of PCOS is approximately 11% among women of childbearing age, and in the structure of endocrine infertility it reaches 70%. The purpose of this study is to develop modern methods of treating infertility in women with polycystic ovary syndrome based on the study of clinical, anamnestic and laboratory parameters, some genotypic variants of gene polymorphisms, and folate metabolism. The results of the studies showed that the cause of chronic anovulation and, as a result, infertility in patients with PCOS can be hormonal abnormalities, which were detected in 82% of patients. The most typical for PCOS was an increase in total testosterone - it occurred in 63.3% of patients, an increase in the LH / FSH ratio of more than 2.5 was observed in 51.3% of patients. With rational treatment of infertility, it is possible to restore fertility in 40% of cases
Keywords: Polycystic ovary syndrome; normalization of body weight; correction of metabolic disorders; stimulation of ovulation